2005
DOI: 10.1128/ec.4.7.1298-1307.2005
|View full text |Cite
|
Sign up to set email alerts
|

Deletion and Allelic Exchange of the Aspergillus fumigatus veA Locus via a Novel Recyclable Marker Module

Abstract: Detailed evaluation of gene functions in an asexual fungus requires advanced methods of molecular biology. For the generation of targeted gene deletions in the opportunistic pathogen Aspergillus fumigatus we designed a novel blaster module allowing dominant selection of transformants due to resistance to phleomycin as well as dominant (counter)selection of a Cre recombinase-mediated marker excision event. For validation purposes we have deleted the A. fumigatus pabaA gene in a wild-type isolate by making use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 63 publications
1
82
0
Order By: Relevance
“…On the other hand, it has been reported that deletion of the veA gene causes a reduction in conidiation capacity in A. parasiticus and A. fumigatus. 17,18) Thus the veA gene appears to be a positive regulator of conidiation in these two Aspergilli. It is likely that it regulates conidiation in various manners among Aspergillus spp.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, it has been reported that deletion of the veA gene causes a reduction in conidiation capacity in A. parasiticus and A. fumigatus. 17,18) Thus the veA gene appears to be a positive regulator of conidiation in these two Aspergilli. It is likely that it regulates conidiation in various manners among Aspergillus spp.…”
Section: Discussionmentioning
confidence: 94%
“…Despite a high level of structural conservation among filamentous ascomycetes, velvet orthologues have divergent roles depending on the fungal species. In N. crassa, A. nidulans and Penicillium chrysogenum, deletion of veA orthologues leads to an increase in light-independent conidial formation, whereas deletion in Aspergillus parasiticus and Aspergillus fumigatus results in a general decrease in conidiation, which is dependent on the nutritional composition of the medium (Bayram et al, 2008;Calvo et al, 2004;Hoff et al, 2010, Krappmann et al, 2005Mooney & Yager, 1990). A reduction in conidiation has also been observed in Aspergillus flavus and Fusarium fujikuroi veA orthologue deletion mutants (Amaike & Keller, 2009;Wiemann et al, 2010).…”
Section: Global Regulation By the Velvet Proteinmentioning
confidence: 95%
“…Various FUdR concentrations have been effectively used in other organisms (Sclafani and Fangman 1986;Sachs et al 1997;Hodson et al 2003;Krappmann et al 2005;Khang et al 2005), and we found that 50 mg/liter FUdR in SC media was sufficient to inhibit growth of the stably integrated TK strains but allow growth of the tk wild-type cells ( Figure 1). As an initial test of our ability to recover newly generated tk wild-type cells, we transformed a strain of S. kudriavzevii that had regions of identical sequence on either side of its hoD::NatMX locus with TkMX PCR product and selected for cells resistant to the antifolate drugs (Figure 2A).…”
Section: Tk Is a Counterselectable Marker In Saccharomycesmentioning
confidence: 85%
“…We have shown that the absence of genes encoding thymidine kinase in almost all fungi allows the selectable and counterselectable HSV-TK gene to be used in several Saccharomyces species. The near kingdom-wide utility of this marker ( Figure S1) has been characterized to a certain extent in a handful of other fungi as well (Sachs et al 1997;Pratt and Aramayo 2002;Hodson et al 2003;Krappmann et al 2005;Khang et al 2005). When paired with an inducible DSB generator, transformation rates approaching 1% of viable cells can be achieved.…”
Section: Discussionmentioning
confidence: 99%